Edukasi Lansia Sehat Bebas Osteoarthritis Lutut di Posyandu Teratai Keprabon - Fendi Gustofa; Arif Pristianto; Yusuf Arianto (UNIB Press, 2023)
The elderly are an age where degenerative diseases often occur, one of the diseases suffered by the elderly is knee osteoarthritis. Knee osteoarthritis (OA) is a degenerative and progressive disease that attacks the knee joints resulting in functional limitations in the elderly. Knee osteoarthritis is caused by an unhealthy lifestyle, lack of exercise, and body weight which are risk factors for knee osteoarthritis. At the posyandu Teratai Keprabon, many elderly people complained of knee pain. This activity is an outreach regarding osteoarthritis and education regarding independent exercise to strengthen and reduce pain in the knee. This activity takes the form of providing leaflets, pre-test, post-test to measure the level of knowledge of the elderly regarding osteoarthritis. Based on the results of filling out the questionnaire, it was seen that the elderly had an increased understanding of osteoarthritis, such as signs and symptoms as well as exercises to reduce pain and strengthen muscles in the knee.